Fe2(so4)3+naoh (нужно составить из этого полное ионное уравнение )

Дура567 Дура567    1   21.05.2019 03:40    1

Ответы
KaraKiller KaraKiller  15.06.2020 00:57

Fe2(So4)3+6NaOH= 3Na2SO4 + 2Fe(OH)3

2Fe+3SO4 +6Na+6OH=6Na+3SO4+2Fe(OH)3

2Fe+6OH=2Fe(OH)3

ПОКАЗАТЬ ОТВЕТЫ
ecuzera2611 ecuzera2611  15.06.2020 00:57

Fe2(SO4)3 + 6NaOH = 2Fe(OH)3(осад.) + 3Na2SO4

 

2Fe(3+) + 3SO4(-2) + 6Na(+1) + 6OH(-1) = FeOH3 + 6Na(-1) + 3SO4(-2) - полное ионное

 

Fe(+3) + 3OH(-1) = FeOH3 - краткое ионное

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Химия